2007
DOI: 10.1111/j.1600-0404.2006.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-convulsive status epilepticus secondary to valproic acid-induced hyperammonemic encephalopathy

Abstract: In conclusion, although uncommon, a possible induction of non-convulsive status epilepticus by valproate-induced hyperammonemic encephalopathy should be taken into account and properly managed by discontinuation of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Her symptoms and EEG findings immediately improved after administration of VPA was stopped. Therefore, we assessed this episode as VPA-induced non-convulsive status epilepticus (NCSE).The frequency of diagnoses of drug-induced NCSE cases has recently increased, and some patients with NCSE due to VPA-induced hyperammonemic encephalopathy (VHE) have been reported [Velioglu and Gazioglu, 2007]. However, in our case, the serum ammonia concentration was within the normal range; therefore, the cause of the patient's NCSE was probably not VHE.…”
mentioning
confidence: 47%
“…Her symptoms and EEG findings immediately improved after administration of VPA was stopped. Therefore, we assessed this episode as VPA-induced non-convulsive status epilepticus (NCSE).The frequency of diagnoses of drug-induced NCSE cases has recently increased, and some patients with NCSE due to VPA-induced hyperammonemic encephalopathy (VHE) have been reported [Velioglu and Gazioglu, 2007]. However, in our case, the serum ammonia concentration was within the normal range; therefore, the cause of the patient's NCSE was probably not VHE.…”
mentioning
confidence: 47%
“…Garg et al [12] reported a patient with neonatal convulsions who presented with VPA-induced hyperammonemiarelated consciousness disturbance and lethargy. Velioğlu et al [13] reported a 19 year-old male with idiopathic generalized epilepsy who exhibited hyperammonemia-induced dizziness, nausea and consciousness disturbance four days after VPA administration. The patient's EEG showed high-voltage sharp waves in the left frontal and temporal regions.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures may arise from toxic levels of AED (phenytoin > 40 μg/mL, carbamazepine > 18 μg/mL) [24], valproate in patients with inborn errors of metabolism [25], lamotrigine overdose [26], drug interactions during polypharmacy, choice of an inappropriate AED for epilepsy type (eg, carbamazepine with myoclonic epilepsy), or a paradoxical reaction to a correct medication. Withdrawal of the inciting AED is the treatment [24].…”
Section: Medications and Dyesmentioning
confidence: 99%